Assessing the Impact of Telecommunications Engineering Teams’ Soft Skills on Job Performance - ADEMOLA, Adewoye Peter; ODUMU, Wesley Odeh (ABUAD Journal of Engineering and Applied Sciences, 2024)
Different project failures that occurred previously all around the world motivated researchers, academics, and business owners to engage in forensic activities to determine the root causes of such failures. Some businesses found that, regardless of the sound technical skills possessed by the personnel who managed the failed projects, the personnel’s lack of soft skills was a major contributing factor toward the project failures. The purpose of the quantitative study was to assess how telecommunications engineering teams’ soft skills could affect the engineers' job performance based on their perceptions. The research was based on the Styron Soft-Skills Competency Framework, which had three clusters of soft skills and was modified into a five-cluster framework. The five clusters formed the basis on which a five-point Likert scale research questionnaire was developed. A pilot study with 7 participants was conducted, after which a total of 46 telecommunications engineers participated in the full study survey. Cronbach’s alpha test was conducted to establish the internal consistency of the survey instrument. The findings of the study showed that financial management soft skills significantly impacted job performance as perceived by the respondents. Recommendations for future research include assessing the impact of the soft skills of engineers on their job performance in other industries and countries.